2011
DOI: 10.1093/pasj/63.sp3.s691
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Terrestrial Diffuse X-Ray Emission Associated with Coronal Mass Ejection and Geomagnetic Storm

Abstract: We present an analysis of a Suzaku observation taken during the geomagnetic storm of 2005 August 23-24. We found time variation of diffuse soft X-ray emission when a coronal mass ejection hit Earth and caused a geomagnetic storm. The diffuse emission consists of fluorescent scattering of solar X-rays and exospheric solar wind charge exchange. The former is characterized by a neutral oxygen emission line due to strong heating of the upper atmosphere during the storm time, while the latter is dominated by a sum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 44 publications
2
46
0
Order By: Relevance
“…Figure 39 shows how contributions from the species-dependent solar wind charge exchange line emissions can be combined with emissions from the nonvariable diffuse sky and contributions from energetic protons to fit a background-subtracted and flare-cleaned XMM-Newton spectrum observed during a coronal mass emission (Carter et al 2010). Ezoe et al (2011) With accurate magnetohydrodynamic models describing the Earth's plasma environment, it should also be possible to infer exospheric neutral densities from soft X-ray observations. Here observations suggest that models underestimate outer exosphere densities.…”
Section: Line Emissions Near Earthmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 39 shows how contributions from the species-dependent solar wind charge exchange line emissions can be combined with emissions from the nonvariable diffuse sky and contributions from energetic protons to fit a background-subtracted and flare-cleaned XMM-Newton spectrum observed during a coronal mass emission (Carter et al 2010). Ezoe et al (2011) With accurate magnetohydrodynamic models describing the Earth's plasma environment, it should also be possible to infer exospheric neutral densities from soft X-ray observations. Here observations suggest that models underestimate outer exosphere densities.…”
Section: Line Emissions Near Earthmentioning
confidence: 99%
“…Here observations suggest that models underestimate outer exosphere densities. Inspecting case and statistical studies of Suzaku observations, both Ezoe et al (2011) andIshikawa (2013) concluded that observed emissions require greater neutral densities beyond 10 R E than current exospheric models predict.…”
Section: Line Emissions Near Earthmentioning
confidence: 99%
“…1) during our observations, we would have in general expected a large increase in the measured X-ray flux and spectral hardness due to the presence of highly charged ions (as shown by the examples of an ICME interacting with the exosphere of the Earth; Ezoe et al 2011;Carter et al 2010). Approximately 10% of ICMEs appear to exhibit only weak compositional anomalies (Richardson & Cane 2004).…”
Section: X-ray Lightcurvementioning
confidence: 85%
“…Roughly 3% of Suzaku observations have detectable SWCX emission (Ishi et al 2017). Some events, such as those studied by Ezoe et al (2010) or Ezoe et al (2011) occurred in the flanks of the magnetosheath. Analyses generally assumed a magnetospheric origin and, given the observing geometry, special effort was made to demonstrate that the excess emission was indeed charge exchange, due to correlation with and lag from solar wind features, rather than scattered solar X-rays.…”
Section: Suzakumentioning
confidence: 99%